SOCIAL MEDIA FOR LEARNING FOR THE ELDERLY - topothai, varangkana (ECT Education and Communication Technology Journal, 2020)
Social media for learning for the elderly is an intermediary which transmits the content, experience, and learning process for behavioral change. Through media that gathers a group of people on the (Internet the computer network); seniors can create, share, exchange knowledge, content, and experience in forms of audio, text, images, animation, and more through the media of the website in the computer network. With these processes, the elderly, and individuals or departments involved in the development of the elderly can communicate with one another. These can be helpful for the elderly to learn or perceive the information, explore new knowledge, ascertain into the interesting topics, communication, and entertainment, seek for business advantage and help to do brainstorming and working together. However, social media should be used with discretion, media literacy, ethics, and safety.